The service abroad of extrajudicial documents: private documents - Elvira Benayas, María Jesús (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
The Court of Justice has established a broad concept of what should be understood by “extrajudicial documents” for the application of the service regulation, which includes private documents. This raises problems in the specification of what documents would be included if the formal transmission of these is necessary “for purposes of exercising, proving or safeguarding a right to a claim in civil or commercial law”.This “new concept” requires a review of the position of the Spanish legislator on the notification of extrajudicial documents not only with respect to the Regulation but also in the application of the Law on International Legal Cooperation in Civil Matters.
Keywords: service abroad; private documents; extrajudicial documents